1998
DOI: 10.1104/pp.117.2.375
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellins Promote Trichome Formation by Up-RegulatingGLABROUS1in Arabidopsis1

Abstract: Trichome development is dependent on gibberellin (GA) signaling in Arabidopsis thaliana. Using the GA-deficient mutant ga1-3, the GA-response mutant spy-5, and uniconazol (a GA-biosynthesis inhibitor), we show that the GA level response correlates positively with both trichome number and trichome branch number. Two genes, GL1 and TTG, are required for trichome initiation. In ga1-3, coexpression of GL1 and R, the maize TTG functional homolog, under control of the constitutive 35S promoter, restored trichome dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
164
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(176 citation statements)
references
References 35 publications
(12 reference statements)
9
164
1
2
Order By: Relevance
“…When 10 µM GA 3 was applied, the transcript levels of GL1, TTG1, and SPY significantly increased or decreased, in a tendency opposite to that in dxr mutant (Figure 7). This result is consistent with the important role of GAs in trichome formation and development [43][44][45].…”
Section: Dxr Transcript Level Affects the Transcription Of Many Genessupporting
confidence: 91%
See 1 more Smart Citation
“…When 10 µM GA 3 was applied, the transcript levels of GL1, TTG1, and SPY significantly increased or decreased, in a tendency opposite to that in dxr mutant (Figure 7). This result is consistent with the important role of GAs in trichome formation and development [43][44][45].…”
Section: Dxr Transcript Level Affects the Transcription Of Many Genessupporting
confidence: 91%
“…In addition to the albino phenotype, we also found trichome initiation and stomata closure defects as a result of DXR disruption. It was previously reported that GAs play important roles in trichome development by regulating trichome-associated genes including GL1, GL3, and SPY [41][42][43][44][45]. As GAs are a class of important products derived from MEP-related isoprenoid biosynthetic pathways, it is reasonable to link DXR disruption to the observed trichome developmental defects.…”
Section: Discussionmentioning
confidence: 99%
“…S4B in the supplementary material) (Larkin et al, 1994). Gibberellins are proposed to activate trichome formation by upregulating GL1 expression (Perazza et al, 1998). Our results, however, suggest that JA signaling activates the function of GL1 protein in an indirect manner.…”
Section: Discrete Domains Of Gl1 Contribute To Trichome Induction Difcontrasting
confidence: 54%
“…GA levels are in picograms per gram of fresh weight. by GAs (Perazza et al, 1998). Recently, it has been shown that FUS3 represses TTG1 expression in the epidermis of embryos (Tsuchiya et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…While ABA biosynthesis is regulated both maternally and zygotically, the control of GA biosynthesis during seed development is largely unknown. Because seed development in Arabidopsis requires two processes-one that is regulated by LEC genes and a second that requires ABA (Raz et al, 2001)-and because trichome formation, a GAdependent process on leaves (Perazza et al, 1998), is observed on lec embryos, we investigated whether the GA pathway was misregulated in lec mutants.…”
mentioning
confidence: 99%